Analysis of Electric Vehicle (EV) Transmission Performance through Helical Rotor Gear Systems with Variable Helix Angles - Hassan, Ali Raad; Jadoo, Aws Taha; Bakhy, Sadeq Hussein; Njim, Emad Kadum; Al-Maliky, Firas Thair (ASEAN Journal of Science and Engineering, 2025)
This study investigates the effect of helix angle on the performance of electric vehicle transmission systems using a helical-rotor-geared test apparatus. Several gears and pinions with different helix angles were manufactured and tested at two rotational speeds. The research combined theoretical modeling and finite element analysis to calculate natural frequencies, followed by vibration analysis using an experimental setup. The Fast Fourier Transform was applied to accelerometer data to evaluate the dynamic behavior. The results showed that larger helix angles reduced vibration amplitude and noise levels. This occurs because smoother meshing at higher angles leads to improved load distribution and lower transmission disturbances. The combination of simulation and physical testing supports the optimization of gear dynamics in electric vehicle powertrains, contributing to quieter and more efficient systems.